Agricultural Management Options for Climate Variability and Change: Microirrigation: HS1203/HS1203, 7/2012 - Zotarelli, Lincoln; Fraisse, Clyde; Dourte, Daniel (EDIS, 2012)
Microirrigation is the slow, frequent application of water directly to relatively small areas adjacent to individual plants through emitters placed along a water delivery line. A leading advantage of microirrigation is that evaporation that does not contribute to plant growth happens much less than with sprinkler irrigation. This 5-page fact sheet was written by Lincoln Zotarelli, Clyde Fraisse, and Daniel Dourte, and published by the UF Department of Horticultural Sciences, July 2012. HS1203/HS1203: Agricultural Management Options for Climate Variability and Change: Microirrigation (ufl.edu)